Microsoft Outlook 2016 : step by step - Lambert, Joan (Step by step (Redmond, Wash.), 2016)
If you're ready to learn Microsoft Outlook 2016, this guide makes the learning easy. Lambert provides brisk lessons and colorful screenshots that show you exactly what to do, step by step. From organizing your inbox to scheduling meetings and tracking tasks, you'll get more done-- quickly!